Strengthening Democratic Characters Through Learning of Pancasila and Citizenship Education in the Era of the Industrial Revolution 4.0 - Saputri, Ravita Mega; Marzuki, Marzuki; Li, Xinxin (Journal of Educational Management and Strategy, 2024)
This study aims to determine the strengthening of the democratic character of students through Pancasila and Citizenship Education in the era of the industrial revolution 4.0 and to identify planning, implementation, evaluation, obstacles and supporters in strengthening the democratic character of Homeschooling Surya Nusantara. This research uses a qualitative approach with a descriptive type. The research subjects were obtained from the principal, teachers and educators. The validity of the data used source and technique triangulation techniques. The data analysis process includes components of data reduction, data presentation, and drawing conclusions. The results of the study show that Pancasila and Citizenship Education teachers in the era of industrial revolution 4.0 must innovate in learning and the media used in the classroom because it does not rule out the possibility that technology can cripple the work of teachers. Apart from innovating in the teaching and learning process as a teacher must be able to instill good character for participants students. It can be seen that Pancasila and citizenship education teachers have a big influence in instilling a democratic character for students in the era of the industrial revolution 4.0.